Optimizing the Performance of Database and Information Systems Architecture through the COBIT 2019 Framework and ITIL V4: A Case Study of PT. Syntax Corporation Indonesia - Mar’atus Solikhah; Vivi Meilinda; Iin Tarsini; Arulfalah Nurwahid; Satrio Rafli Firmansah (Jurnal Indonesia Sosial Teknologi, 2025)
The background of this research focuses on the application of COBIT 2019 and ITIL v4 to improve the performance of information systems and IT management in a company. Along with the rapid development of information technology, organizations are faced with the challenge of optimizing IT management to be more efficient and integrated with business goals. COBIT 2019 offers a framework for holistic IT governance, while ITIL v4 focuses on managing IT services that are more responsive to user needs. The purpose of this study is to analyze and compare the application of the two frameworks in improving the performance of information systems and IT service management, as well as to see their impact on operational efficiency and service quality in the company. The method used is a quantitative descriptive approach with case studies in companies that have implemented both frameworks. Data was collected through observations, interviews, and questionnaires involving IT staff, IT managers, and system users. The results of the study show that the implementation of COBIT 2019 has succeeded in improving IT governance management, while the implementation of ITIL v4 has proven to be effective in improving IT service management. Both frameworks have a positive impact on the performance of databases and IT services, with significant improvements in query response time, data consistency, and reduced system downtime.